OPTIMALISASI DANA ZAKAT, INFAK DAN SEDEKAH MASJID TERADAP PEMBERDAYAAN JAMAAH (Studi di Masjid Imam Rijali IAIN Ambon) - Mossy, Julianty Ryzkha L (Al-Qashdu : Jurnal Ekonomi dan Keuangan Syariah, 2021)
The purpose of this study is to describe the form of empowering the congregation of the Imam Rijali mosque IAIN Ambon and to find out the efforts of the mosque takmir in optimizing funds Zakat, Infak and Alms (ZIS) to the congregation of the Imam Rijali mosque IAIN Ambon through observation and interviews with takmir The results of this study conclude that the forms of empowering the congregation of Imam Rijali Mosque IAIN Ambon include: religious spiritual empowerment, educational empowerment, and social empowerment intersect and support each other in improving community welfare and improving the quality of life ZIS funds are allocated for empowerment optimization programs at Islamic boarding schools, orphanages and students around the mosque who do not return home during Eid, while infaq and shadaqah funds received are optimized for the physical improvement of mosques, and non-physically infaq funds are optimized to facilitate rehabilitation. The maja of the mosque is approximately 7 people who function to maintain the cleanliness of the mosque and the programs carried out for recitation, cadre of imams, muballiqh and da'i.